The role of yield stress on cracked thin panels of aluminum alloys repaired with a fRP patch. Issue 5 (16th April 2017) - Shinde, P. S.; Kumar, P.; Singh, K. K.; Tripathi, V. K.; Aradhi, S.; Sarkar, P. K.
ABSTRACT: The aim of this study was to explore the effect of the yield stress of the cracked thin panels of aluminum alloys panel, repaired with one sided fiber reinforced polymer (FRP) patch, on the performance of the repair. Various different grades of aluminum alloys with thickness in the range of 1–1.3 mm were used as the skin material. The numerical simulation of the experimental results was done through ANSYS 15.0, using a cohesive zone material model (CZM model) at the interface of the skin and the patch. The effect of the far field applied stress was analyzed to simulate the initiation and the separation of the patch. In all the six cases, undertaken in this study, the patch separation occurred when the applied stress exceeded the yield stress of the skin by a small percentage. Even in the thinnest patch with its stiffness ratio of 0.28, the patch separated when the applied stress exceeded the yield strength of the skin material. In all the cases, the shear stress at the interface caused the slippage between the patch and the skin at the leading edge of the patch.